0805 Lack of Association Between Periodic Limb Movements of Sleep and Neuroimaging Signatures of Cerebral Small Vessel Disease in Stroke-Free Community-Dwelling Older Adults. (27th May 2020) - Slota, K A; Castillo, P; Mera, R M; Del Brutto, V J; Del Brutto, O H
Abstract: Introduction: Evidence of the relationship between periodic limb movements during sleep (PLMS) and cerebral small vessel disease (cSVD) is limited and inconsistent. Here, we aimed to assess the independent association between PLMS and the different neuroimaging signatures of cSVD. Methods: Community dwelling adults aged ≥60 years enrolled in the Atahualpa Project undergoing PSG and MRI with time intervals ≤6 months were included. MRI readings focused on white matter hyperintensities (WMH) of presumed vascular origin, deep cerebral microbleeds (CMB), silent lacunar infarcts (LI), and >10 enlarged basal ganglia-perivascular spaces (BG-PVS). Data from single-night polysomnograms were interpreted according to recommendations of the American Academy of Sleep Medicine. Associations between the PLMS index and neuroimaging signatures of cSVD (as dependent variables) were assessed by means of logistic regression models, adjusted for relevant confounders. Results: A total of 146 individuals (mean age: 71.4 ± 7.5 years; 64% women) were included. A PLMS index ≥15/hour were noted in 48 (33%) participants. Moderate-to-severe WMH were present in 33 individuals (23%), deep CMB in 9 (6%), silent LI in 16 (11%), and >10 BG-PVS in 44 (30%). In univariate analyses, silent LI ( p =0.035) and the presence of >10 enlarged BG-PVS ( p =0.034) were significantly higher among participants with a PLMS index ≥15/hour. However, fully-adjusted multivariate models showed no significant association between PLMS index ≥15/hour and any of the neuroimaging signatures of cSVD. Conclusion: This study shows no independent association between the PLMS index and neuroimaging signatures of cSVD in stroke-free community-dwelling older adults. Support: This study was supported by Universidad Espíritu Santo - Ecuador.